Density dependence in induced plant resistance to herbivore damage: threshold, strength and genetic variation - Underwood, Nora (Oikos, 2000)
The density-dependent effect of induced plant resistance on herbivore populations depends on the relationship between the amount of herbivore damage and the level of induced resistance produced by the plant. This relationship should influence the interaction of induced resistance and herbivore population dynamics, and if the relationship varies among plant genotypes, it could be subject to natural selection by herbivores. In this study the relationship between percent leaf area damaged and level of induced resistance was characterized for four genotypes of soybeans grown in a greenhouse. Damage ranging from 8 to 92% of leaf area was imposed using Mexican bean beetle larvae, and induced resistance was measured by bioassay using Mexican bean beetle adults. The level of induced resistance was significantly affected by the amount of damage, and the level of induced resistance varied significantly among the four genotypes. There was also a marginally significant interaction of damage and plant genotype, suggesting that the form of density dependence varies among these four genotypes of soybeans. These results suggest that these genotypes of plants might affect herbivore populations differently. If this variation is heritable, the form of density-dependent effects of induced resistance has the potential to evolve in this system.